Disputes concerning honour among the subjects of Pardubice estate (Theatrum historiae, 2009)
After short introduction to theoretical concepts of honour article deals with different conceptions of masculine and female honour. On the basis of concrete disputes solved by lower courts of Pardubice estate small towns and manorial court author tries to define attributes which distinguished honour of men and women. She pursues male and female characteristics connected with behaviour which could put honour at risk. Except the form and content of offenses she analyses abuses used against men and women and she pursues places where disputes of honour took place. She takes notice that this type of disputes was mainly male domain. Male honour was more public affair and related particularly to credibility and qualities connected with work. Female honour was rather private and personal business and was connected with sexual behaviour.